2013
DOI: 10.1016/j.anireprosci.2013.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Plasma progesterone changes and length of oestrous cycle in Rusa Deer (Rusa timorensis)

Abstract: A study was conducted to profile the plasma progesterone (P4) concentrations and establish the length of oestrous cycle in the Rusa timorensis during the breeding season. Five healthy hinds were selected for peripheral blood sampling twice weekly to gauge the P4 levels by radioimmunoassay, at the start of the breeding season indicated by rutting behaviours of sexually active males. The hinds were polyestrous as proven by the cyclic trend of P4 levels. After the presumptive oestrus indicated by the lowest P4 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The minimal sexual behaviors displayed by the female individuals, except during the peak periods, may indicate a more selective and receptive mating strategy (Ciuti and Apollonio, 2016). The minimal sexual behaviors exhibited by the female deer suggest the possibility of behavioral observation in females to estimate estrus reliably (Mahre et al, 2013) Estimating the estrus period is crucial for successful reproductive management since the fertilization window is limited. The result from this study indicated that there are two distinct peaks in male sexual behavior, which coincided with the estrus behaviors of the female deer.…”
Section: Resultsmentioning
confidence: 99%
“…The minimal sexual behaviors displayed by the female individuals, except during the peak periods, may indicate a more selective and receptive mating strategy (Ciuti and Apollonio, 2016). The minimal sexual behaviors exhibited by the female deer suggest the possibility of behavioral observation in females to estimate estrus reliably (Mahre et al, 2013) Estimating the estrus period is crucial for successful reproductive management since the fertilization window is limited. The result from this study indicated that there are two distinct peaks in male sexual behavior, which coincided with the estrus behaviors of the female deer.…”
Section: Resultsmentioning
confidence: 99%
“…In the previous study, the estrous cycle length during the breeding season of the female Rusa deer, inhabiting tropical Peninsular Malaysia, was 19.2 days, based on plasma concentration of progesterone [14]. A future study will examine detail pattern of fecal progesterone and 17β-estradiol metabolites by more frequent sampling to determine exact the estrous cycle length of Rusa deer in Thailand.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the understanding of Rusa deer reproduction not only has economic benefits for deer farming operations, but also represents a model for endangered deer species in Thailand. The major breeding activity was observed in plasma progesterone of female Rusa deer in Malaysia under appropriate environmental conditions and high nutrition in March to July [14]. After 8 months of gestation, adult hinds generally give birth with a single calf.…”
mentioning
confidence: 99%